Common fixed point theorems in complex valued non-negative extended b-metric space - Naimat Ullah; Mohammed Shehu Shagari; Tahir Ahmad Khan; Aziz Ullah Khan; Muhammad Atta Ullah Khan (E-Journal of Analysis and Applied Mathematics)
We introduce complex valued non-negative extended b-metric spaces and establish new fixed point results for mappings under some rational contractions. Our idea improves and extends corresponding fixed point theorems in the setting of b-metric, extended b-metric and classical metric spaces. Nontrivial examples are provided to support the hypotheses and usefulness of the main result obtained herein.